Study of Urban Temperature Profiles on Various Land Covers in The Greater Jakarta Region, Indonesia - Fauzi, Rahmad; Arifin, Hadi Susilo; Perdinan, (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
The greater Jakarta is an intimate urban area that evolved into the largest integrated metropolis in Indonesia. It plays a significant role in social, economic, and political aspects. To be considered seriously, however, is the lack of planning capacity in increasingly complex area management. This study seeks to determine urban temperature profiles, classify land cover, and analyze surface albedo in Jakarta greater area. Firstly, the temperature profile is analyzed using nine years of diurnal temperature data. Secondly, land cover classification was analyzed using Landsat 7 ETM+ and Landsat 8 OLI/TIRS image datasets. Thirdly, surface albedo analysis was conducted using previously derived spatial data and land cover characteristics. Results of the temperature profile indicate that urban areas have a longer cooling period than suburban areas. The classification procedure yields seven classes of land cover with an accuracy rate of 80.95% (2010) and 83.33% (2018); the kappa coefficient is 0.74 (2010) and 0.77 (2018), respectively. Since 2010, urban areas have expanded, as can be deduced from the evidence. The distribution of surface albedo values from high to low includes built-up land, grass/shrubs, vegetation, water bodies, and moist soil. Additionally, surface albedo and air temperature positively correlate with land cover variations. This is demonstrated by the high R-square values between albedo and land cover (0.84 and 0.90) and air temperature and land cover (0.59 and 0.60). In other words, land cover changes can increase albedo and air temperature.